PENGARUH PEMASANGAN FILTER UDARA TERHADAP PERFORMA MESIN VESPA SPRINT 150cc - Anam, Khoirul; Prasetyo, Imam; Firdan, Muhammad (Universitas Muhammadiyah Pekajangan Pekalongan, 2020)
ABSTRACTNow a means of transportation that are rarely loved by the public are old vehicles which are now rarely found in the community. Such as the problem that is often found is that old vehicles have decreased inperformance and spare parts are difficult to find. This study aims to determine the effect of the carburetor filter on motorcycle engine performance. The research was conducted with an experimental method using a VESPA SPRINT V 150cc bicycle in 1975. The carburetor filter was varied, namely testing the standard filter, testing without filters. Experiments were carried out using the dynotest test tool. Measurement of engine speed and dynotest roller rotation. Premium fuel consumtion meansurement. The test result data is processed to obtain power and torque. The results of these calculations are displayed in tables and graphs. Based on the test result, it is found that the maximum power increases without an air filter with a result of 6.0hp at 8013rpm while the maximum torque increases with an air filter with a result of 6.0nm at 6268rpm.Keywords : Performance, Air Filter, Vespa.